PENGEMBANGAN MULTIMEDIA INTERAKTIF UNTUK PEMBELAJARAN MATERI POKOK BALOK SISWA SMP KELAS VIII - Hardiyanto, Edwin Latif; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The purposes of this study were: (1) to develop a valid interactive multimedia learning as a source of student learning in understanding the topic of Cuboid of eight grade students; and (2) to know the effectiveness of learning interactive multimedia products which had been developed. This research was a development study using Borg & Gall model where the steps as follows: (1) preliminary study that consisted of literature study and field study; (2) development that consisted of purpose analysis, capability analysis, development design; (3) field test that consisted of limited field test, wider field test and operational test; (4) effectiveness test; (5) dissemination. The research population was all eight grade students of SMPN 2 Ponorogo.The sample was taken using cluster random sampling. Data were collected in the form of even UTS value 2013/2014 in mathematics subject used documentation method the validity of product used questionnaire method, the learning results in mathematics used test method. The validity of the developed interactive multimedia product used content validity by material expert and media expert.The validity of test item was determined by: (1) content validity; (2) discrimination power; (3) difficulty level; (4) reliability. The normality test used Lilliefors method and homogeneity of variance test used Bartlett method. The balanced and the hypothesis test used t-test statistic. The results of this study were as follows: (1) a valid interactive multimedia learning as a source of student learning in understanding mathematics of eight grade students of SMP especially Cuboid; (2) the result of effectiveness test showed that the mathematics learning results of students who used interactive multimedia were better than students who did not use interactive multimedia learning.Keywords: Development, Interactive Multimedia, Interactive Multimedia Learning